TINJAUAN KESEDIAAN AIR BERSIH IBUKOTA KECAMATAN SUWAWA KABUPATEN BONE BOLANGO - Nusu, Olgha; Maulidiyah, Yesi (Universitas Bina Taruna Gorontalo, 2013)
ABSTRAK Suwawa capital district, located in the district of Bone Bolango. Geographically located at 0o 19 '55